Analysis of the Quality of Public Services in the Job Training Program at the Dumai City Manpower Office - Erinaldi, Erinaldi; Wiharni, Ajeng Putri; Elfrida, Mei Rina; Susela, Rukma; Alfianti, Suci (CV. Civiliza Publishing, 2026)
The high unemployment rate in Indonesia is a problem that has a wide impact on the social and economic conditions of the community. The increase in the number of labor forces that is not balanced with the availability of jobs requires strategic efforts from the government, one of which is through the implementation of job training programs. This program not only aims to improve the competence of the workforce, but is also a form of public service that must be carried out in a quality manner. This research aims to analyze the quality of public services in the implementation of job training programs at the Dumai City Manpower Office. This study uses a descriptive qualitative approach with data collection techniques through observation and documentation. The analysis was carried out using the SERVQUAL concept which includes five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of the study show that the quality of public services in job training programs in general is in the category of quite good. The aspects of reliability, responsiveness, and assurance show good performance, characterized by the implementation of structured programs, the suitability of training materials with the needs of the job market, and the competence of instructors who provide quality assurance of training. However, in the aspect of tangibles and empathy, obstacles are still found, especially the limited facilities and training capacity that have not been able to reach all job seekers, so that it has an impact on uneven access to services. Thus, it can be concluded that even though the job training program has been run in accordance with procedures, the quality of services provided still needs to be improved, especially in terms of equitable access and optimization of training capacity, in order to provide wider benefits to the community.